DLCO response to experimental cycle-run succession in triathletes - Hue, O.; Le Gallais, D.; Boussana, A.; Prefaut, C. (2001)
BACKGROUND: We still know relatively little about the factors that define the ability to perform a good run after cycling in triathlon, however, and the perception of discomfort during the first minutes of this post-cycling running has yet to be satisfactorily explained. The pulmonary diffusion capacity for carbon monoxide (DLCO) has been demonstrated to be impaired after the cycle-run succession. Numerous causes have been suggested to explain this phenomenon, but the exact mechanism has not yet been determined. METHODS: Thirteen young male triathletes participated in four different exercise trials: 30 min of cycling followed by 20 min of running (C-R, 1 min rest between C and R), 30 min of running followed by 20 min of running (R-R, 1 min rest between R and R), 30 min of cycling (C), and 30 min of running (R). DLCO and alveolar volume were simultaneously measured during 9 sec of breath-holding before and 10 min after exercise. The transfer coefficient (KCO=DLCO/VA) was then calculated. During all trials, ventilatory data were collected every minute using an automated breath-by-breath system. RESULTS: The results showed that 1) C-R and C induced significant and identical decreases in DLCO and KCO in post-trial compared with pre-trial measurement (40.41+/-2.24 vs 43.49+/-2.36 ml.min-1.mm.Hg-1, p<0.01, and 39.37+/-2.16 vs 42.99+/-2.38 ml.min-1.mm.Hg-1, p<0.02, for C-R and C, respectively) and 2) there were no DLCO decreases in post-trial compared with pre-trial measurement in R-R and R. CONCLUSIONS: We concluded that cycling exercise in itself seems to increase the immediate post-exercise DLCO impairment.